Current Status and Countermeasures of High Quality Grain Industry in Hua County - Li, Chong (Journal of Global Economy, Business and Finance, 2024)
The high-quality development of the grain industry is a solid foundation for ensuring national food security and comprehensively promoting rural revitalization. The grain industry in Hua County presents the trend of the steady improvement of the comprehensive grain production capacity, the enhancement of the grain processing capacity, the continuous improvement of the level of agricultural mechanization, and the rapid development of the modern seed industry. At the same time, there are also problems such as low grain production efficiency, low degree of grain branding, and low degree of "three-chain isomorphism" in grain industry. In view of the above problems, the countermeasures are mainly proposed from the aspects of farmland infrastructure construction, modern seed industry and agricultural technology service, farmers' interest compensation mechanism, branding and scientific and technological innovation, in order to solve the current prominent contradiction in grain production and provide reference for promoting the high-quality development of grain industry in Hua County.